Effect of gamification approach towards mastery of al-'Adad wa al-Ma'dud among secondary school students - Che Ku Mohamad, Che Ku Nor Asiah; Hassan, Abd Rauf; Mohamad, Ab Halim; Mustapha, Nik Farhan (Human Resource Management Academic Research Society, 2020)
The issue of poor mastery of Arabic grammar among students is nothing new. Many studies have been done by previous researchers on this matter. One of the topics that is considered difficult and confusing is the topic of al-'Adad wa al-Ma'dud. Studies show that factors affecting students' difficulty in mastering any educational topic are closely related to the techniques or approaches to teaching. Therefore, this study aims to identify the level of al-'Adad wa al-Ma'dud dominance among form six students, to analyse the effect of gamification approach and comparing the al-'Adad wa al-Ma'dud level of mastery between the control and experimental groups as well as comparing al-'Adad wa al-Ma'dud level of mastery between male and female students. The quasi-experimental method was implemented using pre-and post-test questionnaires. The sample of this study was 60 students in sixth form at Ma’ahad Ahmadi Gemencheh, Negeri Sembilan. The students were divided into two groups, the control group (n = 30) and the experimental group (n = 30). Data were analysed descriptively to obtain frequency, percentage and mean. A t- test was conducted to measure differences in the level of mastery of the two groups. The findings show that the level of mastery for al-'Adad wa al-Ma'dud was low for both the control and experimental groups before treatment. After the gamification approach was given to the experimental group, the findings showed a positive impact on al-'Adad wa al-Ma'dud dominance with an improvement in the level of al-'Adad wa al-Ma'dud for the experimental group was higher than that of the treatment group after the gamification approach was used. As for the level of al-'Adad wa al-Ma'dud dominance between male and female students, the findings show no significant differences by gender. It is hoped that this study will be able to assist Arabic language educators apply a gamification approach to teaching and learning grammar in the Arabic language, in particular the topic of al-'Adad wa al-Ma'dud.